Exploring a role for fatty acid synthase in prostate cancer cell migration. (4th July 2021) - De Piano, Mario; Manuelli, Valeria; Zadra, Giorgia; Loda, Massimo; Muir, Gordon; Chandra, Ash; Morris, Jonathan; Van Hemelrijck, Mieke; Wells, Claire M.
ABSTRACT: Fatty acid synthase (FASN) is commonly overexpressed in prostate cancer and associated with tumour progression. FASN is responsible for de novo synthesis of the fatty acid palmitate; the building block for protein palmitoylation. A functional role for FASN in regulating cell proliferation is widely accepted. We recently reported that FASN activity can also mediate prostate cancer HGF-mediated cell motility. Moreover, we found that modulation of FASN expression specifically impacts on the palmitoylation of RhoU. Findings we will describe here. We now report that loss of FASN expression also impairs HGF-mediated cell dissociation responses. Taken together our results provide compelling evidence that FASN activity directly promotes cell migration and supports FASN as a potential therapeutic target in metastatic prostate cancer.